2019
DOI: 10.1002/ejsp.2597
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐couple similarity in dyadic coping and partners’ adjustment to the birth of a child

Abstract: Unlike individual perceptions of a couple's functioning, couple‐level protective factors against poor adjustment to the birth of a child have rarely been studied. This study examined similarity or reciprocal exchanges in dyadic coping (DC) during pregnancy (T1) and at 6 weeks postpartum (T2) and its associations with both partners’ adjustment at 6–9 months postpartum (T3). Ninety‐two Portuguese couples provided data on DC, internalizing symptoms, dyadic adjustment and parenting stress. An individual's perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…However, contrary to these studies, we found actor but not partner effects between common DC and partners' adjustment (which did not confirm our hypothesis 2b). Although actor effects are, generally, stronger than partner effects in dyadic research (Kenny et al, 2006), it is interesting to note that, considering the results of Alves et al (2019Alves et al ( , 2020, partner effects of DC seem to be especially salient when DC is assessed after than before childbirth. The period soon after childbirth is likely to reinforce partner's dependence in one another, as the birth of a baby affects both partners at the same time and as a unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contrary to these studies, we found actor but not partner effects between common DC and partners' adjustment (which did not confirm our hypothesis 2b). Although actor effects are, generally, stronger than partner effects in dyadic research (Kenny et al, 2006), it is interesting to note that, considering the results of Alves et al (2019Alves et al ( , 2020, partner effects of DC seem to be especially salient when DC is assessed after than before childbirth. The period soon after childbirth is likely to reinforce partner's dependence in one another, as the birth of a baby affects both partners at the same time and as a unit.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on DC during the transition to parenthood is relatively recent and yields initial evidence of the associations between DC and dyadic adjustment ( Molgora et al, 2019 ; Brandão et al, 2020 ), depressive symptoms ( Alves et al, 2018 ), and QoL ( Brandão et al, 2020 ) during pregnancy. Recently, two prospective longitudinal studies also showed that common DC and perceived similarity in DC within the couple influenced partners’ individual and parental adjustment after childbirth ( Alves et al, 2019 , 2020 ). Stress communication and positive DC strategies have been found to be negatively associated with depressive symptoms ( Rottmann et al, 2015 ) and positively associated with QoL in couples experiencing several health conditions ( Meier et al, 2011 ; Vaske et al, 2015 ; Ernst et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Above and beyond the beneficial effect of DC itself, a curvilinear effect of perceived equity in DC on depressive symptoms was found: underbenefit (providing more DC than receiving) and overbenefit (receiving more DC than providing) of DC in women was associated with more depressive symptoms of oneself and the male partner (Meier et al, 2020). However, another study (Alves et al, 2020a) suggests different effects of equity in DC depending on the specific time point during the TTP: one partner’s equity in DC during pregnancy positively predicted internalizing symptoms 6–9 months postpartum, whereas more equity in DC at 6 weeks postpartum predicted less depressive symptoms 6–9 months postpartum. This leads to the conclusion that similarity within the couple after childbirth seemed to be beneficial for both partners.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to the conclusion that similarity within the couple after childbirth seemed to be beneficial for both partners. While during pregnancy being complementary in DC seemed to be more beneficial in the long term, since there may be different needs of support during pregnancy between men and women (Alves et al, 2020a). Interestingly, men and women seem to be influenced differently by the partner’s stress communication in terms of psychological symptoms: higher stress communication by women during pregnancy was associated with higher internalizing symptoms of men at 6 weeks postpartum which was not the case for men’s stress communication (Alves et al, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with the large attention this construct has received in the close relationships' literature, only a few studies have investigated dyadic coping behaviors during the transition to parenthood. Available evidence to date has recognized how dyadic coping is associated with dyadic adjustment (Alves et al, 2018(Alves et al, , 2020(Alves et al, , 2019Brandāo et al, 2020;Molgora et al, 2019). Specifically, Alves et al (2019) highlighted that common dyadic coping efforts are crucial in the postpartum, as demonstrated by the fact that lower scores of common dyadic coping at 6 weeks postpartum predicted higher levels of parenting stress and lower levels of parental confidence at 6-9 months postpartum.…”
Section: Introductionmentioning
confidence: 99%